(untitled) (2014)
Montrichardia linifera is commonly known in Brazil as “aninga.” In November 2008 and August 2009, we collected plant samples and extracted leaves and stems using hexane or dichloromethane and methanol to evaluate its biological and chemical potential, phytochemical profile and polyphenol content. Differences in the chemical composition of the collections were evident. In the first collection, the apolar extracts were the richest in metabolite composition while the polar extracts were the richest in the second collection. In general, extracts from Aug/2009 had higher antioxidant and cytotoxic activities than extracts from Nov/2008 and the stem and leaf extracts from the Aug/2009 collection showed the highest polyphenol content. As an insecticide against Sitophilus zeamais, the hexane extract of the leaves (Aug/2009) presented concentration-dependent insecticidal activity. Only the methanolic extract of stems and leaves (Aug/2009) presented a small inhibition halo (9 and 7 mm, respectively) against Aeromonas hydrophila when evaluating its antibacterial potential. The study demonstrates that, collection period is an important factor to consider in phytochemical and biological activity studies of M. linifera.